2017
DOI: 10.1080/02602938.2017.1300636
|View full text |Cite
|
Sign up to set email alerts
|

Are we educating educators about academic integrity? A study of UK higher education textbooks

Abstract: A substantial proportion of university students report committing plagiarism and related forms of misconduct. An academic integrity-focused approach to addressing plagiarism emphasises the promotion of positive values alongside education of staff and students about good, and bad, practise in writing, studying and assessment design. The concept was developed many years ago and is seen as desirable, yet it is not clear whether academic integrity features prominently in the education of academics themselves. We a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…Initial searches were made using Google Scholar using basic terms relating to contract cheating, identified using the experience of the author (Wallace and Newton, 2014;Newton, 2015;Newton and Lang, 2016;Ransome and Newton, 2017).…”
Section: Identifying Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…Initial searches were made using Google Scholar using basic terms relating to contract cheating, identified using the experience of the author (Wallace and Newton, 2014;Newton, 2015;Newton and Lang, 2016;Ransome and Newton, 2017).…”
Section: Identifying Samplesmentioning
confidence: 99%
“…Improvements to assessment design, education, policy and the law all need to implemented in order to protect academic standards and quality, and the security of a university award. The use of face to face assessment methods (Newton and Lang, 2016), improved education and support for students (Newton, 2015) and staff (Ransome and Newton, 2017) and changes to the law to make provision of commercial contract cheating services illegal could all limit the influence of contract cheating in Higher Education.…”
Section: Summary Of Recommendations For Policy On Commercial Contractmentioning
confidence: 99%
“…Statistics Anxiety has negative consequences for individuals [13,14], including engagement in academically unethical acts [10,15,16]. These are part of an intensifying trend toward academic misbehavior such as plagiarism and cheating [17][18][19]. Academic dishonesty, i.e., unethical academic behavior, is also a practical issue questioning learning's effectivity in the long run.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, academic staff need more continuing professional development on academic misconduct, the forms it can take, and methods to reduce the likelihood of cheating. A UK study of the content of higher education texts (Ransome and Newton 2018) found that academic integrity is poorly addressed and that contemporary issues such as contract cheating are not part of this discourse. In the current study, best practice assessment design was considered crucial to preventing academic misconduct, however there was an acknowledgement that cheating can occur no matter the form.…”
Section: Discussionmentioning
confidence: 99%